Odd–even effect in the formation and extraction performance of Ionic-Liquid-Based aqueous biphasic systems - Belchior, Diana C. V. (2020)
Ionic-liquid-based aqueous biphasic systems (IL-based ABS) have been extensively investigated in the separation of high-value biomolecules. However, the understanding of the molecular-level mechanisms ruling phase separation and extraction performance of these systems is crucial to successfully design effective separation processes. In this work, IL-based ABS composed of K2HPO4 and cholinium carboxylate ILs ([Ch][CnCO2] with n = 1 to 7, comprising anions with odd and even alkyl chain length) were investigated. The respective ternary phase diagrams, including binodal curves, tie-lengths, tie-line lengths and critical points, as well as the Setschenow salting-out coefficients (ks) that is a quantitative measure of the two-phase formation ability, were determined at 298 K. The extraction performance of these systems was then evaluated for four amino acids (L-tryptophan, L-phenylalanine, L-tyrosine, L-3,4-dihydroxyphenylalanine/L-dopa). It was found that ILs composed of anions with even alkyl chains display slightly higher ks values, meaning that these ILs are more easily salted-out or more easily phase separate to form ABS. On the other hand, ABS formed by ILs with anions comprising odd alkyl chains lead to slightly higher partition coefficients of amino acids. Beyond the neat ILs odd-even effect resulting from their nanostructuration, being this a well-known phenomenon occurring in a series of their thermophysical properties, it is here shown the existence of an odd-even effect displayed by the IL anion aliphatic moiety in aqueous solution, visible both in the two-phase formation ability and extraction performance of ABS. These findings contribute to elucidate the molecular-level mechanisms governing ABS formation and partitioning of biomolecules, ultimately allowing the design of effective separation platforms.